Human three‐dimensional dental pulp organoid model for toxicity screening of dental materials on dental pulp cells and tissue. (16th October 2021) - Xu, Xiaoqi; Li, Zheng; Ai, Xiaoqing; Tang, Yin; Yang, Deqin; Dou, Lei
Abstract: Aim: To establish a 3D model for screening the biocompatibility of dental materials/drugs on dental pulp cells and tissue. Methodology: Human dental pulp cells (hDPC) and endothelial cells (EC) were mixed with or without human dental pulp derived extracellular matrix (hDP‐ECM) according to several protocols and cultured in 3D plates to fabricate 3D organoids. Cell viability and proliferation in organoids were evaluated using Live/Dead cell viability assay and ATPase assay. Organoids were fixed, cut and stained with a H&E staining kit. The expressions of DSPP, DMP‐1, CD31, vWF and COL1A in 3D organoids were evaluated using immunofluorescence. To assess the feasibility of 3D organoids on drug/material toxicity screening, the organoids were treated with lipopolysaccharides (LPS) or iRoot BP. Then, cell viability and apoptosis were assessed. The expressions of IL‐6, TNF‐α, and IL‐1β were compared in LPS‐treated and non‐treated organoids. Alizarin Red S staining was used to evaluate calcium deposit formation in organoids. Data were analysed using one‐way anova followed by Tukey's post hoc comparison. Results: The 3D spheres/organoids were formed at day 1 or day 2. Cells in 3D organoids maintained a high viability rate and low proliferation activity. The level of CD31 increased significantly ( p  < .05) when EC were added to coculture with hDPC. The expressions of odontogenesis‐associated proteins (DSPP, COL1A) upregulated ( p  < .05) with the addition of hDP‐ECM. Level of IL‐6 expression and rates of dead and apoptotic cells in 3D organoids were increased significantly ( p  < .05) in response to LPS. Calcium deposit formation was observed in iRoot BP‐treated organoids. Conclusions: Coculture of hDPC and EC in the presence of hDP‐ECM formed functional dental pulp organoids. The experimental model provides an alternative tool for toxicity screening of dental pulp capping agents and dental pulp regeneration research.